Laser welding of high Si-Al alloy - Wong, Xin Yu (2017)
Over the years, Silicon-Aluminum (Si-Al) alloy has been used in various industries such as the aerospace industry as well as for the high-duty electrical packaging. Mechanical properties of the Si-Al alloy include the high strength-to-weight ratio, higher wear resistance and low thermal expansion coefficient. However, laser welding of the alloy has proven to be difficult because of the defects found in the welds. In this project, the laser welded 50% Si-Al alloy is studied to obtain the defects and how the microstructure affects the properties. Looking at the microstructure of the alloy, three phases are obtained, namely the primary silicon particles, eutectic silicon and α-Al. The size, morphology and distribution of the primary silicon particles influence the mechanical properties. The finer and uniform the primary silicon particles is, the better the mechanical properties. Micro-hardness test is conducted on the three zones, fusion zone, heat-affected-zone (HAZ) and the base metal. The fusion zone is found to have the highest hardness out of the three zones, suggesting that it consists of the finest grains. Defects in the laser welds include lack of fusion, porosity and oxide inclusions. Incomplete fusion is the result of poor welding techniques. Too little heat input is unable to make the metals molten enough to weld together. This could also cause crack initiation which ultimately leads to the failure of the alloy. Porosity can be in the form of hydrogen porosity and porosity caused by the instability of the keyhole. Hydrogen porosity depends greatly on the solidification rate. The fast solidification rate leads to the hydrogen unable to escape, resulting it to be trapped inside the weld forming pores. Instability of the keyhole can be reduced significantly by controlling the welding parameters. Shorter wavelength lasers such as the Nd:YAG and the use of high welding speed and low heat input help to produce stable keyhole. Oxide inclusions formed during the laser welding process where the aluminum oxide reacts with air. To avoid such occurrence, it is important to ensure the cleanliness of the working station.